2014
DOI: 10.1155/2014/568317
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing the Number of Tardy Jobs on a Single Machine with an Availability Constraint

Abstract: Most scheduling problems are based on the assumption that machines work continuously during the planning horizon. This assumption is not true in many production environments because the machine may not be available during one or more periods such as during breakdowns or maintenance operations. In this paper, the problem of the single machine scheduling with one unavailability period and nonresumable jobs with the aim of minimizing the number of tardy jobs is studied. A number of theorems are proved and a heuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…And lemma 12. 4 The answer to the instance of Partition is "yes" if and only if the answer to the Decision Variant of Weighted Number of Late Jobs problem (DVWNLJ) is "yes". Same with lemma 12.1, lemma 12.3 can also be proved by induction.…”
Section: Minimizing the Weighted Number Of Tardy Jobsmentioning
confidence: 99%
“…And lemma 12. 4 The answer to the instance of Partition is "yes" if and only if the answer to the Decision Variant of Weighted Number of Late Jobs problem (DVWNLJ) is "yes". Same with lemma 12.1, lemma 12.3 can also be proved by induction.…”
Section: Minimizing the Weighted Number Of Tardy Jobsmentioning
confidence: 99%
“…Different types of aging effect model are addressed and the authors showed that all the cases can be solved optimally in polynomial time. Molaee and Moslehi [31] considered the problem of scheduling jobs on a single machine with one unavailability period to minimize the number of tardy jobs. A branch-and-bound methodology that employed efficient dominance rules is developed to optimally solve the problem.…”
Section: Introductionmentioning
confidence: 99%